Why do goose parents adopt unrelated goslings?:A review of hypotheses and empirical evidence, and new research questions - Kalmbach, E (Ibis, 2006)
Adoption of unrelated offspring by successful breeders is one form of brood mixing and alloparental care that is widespread among geese and other waterfowl. Biparental care and long-lasting family bonds in geese are likely to affect the costs and benefits of adoption. Most hypotheses that have been proposed to explain this behaviour assume that the separation of the gosling from its original family is accidental, and that adoption forms the 'best of a bad job' solution. For the gosling, adoption is therefore thought to be the only, and thus adaptive, option. For parents, some hypotheses assume that there are costs of adoption (intergeneration conflict), while others assume that there are benefits (mutually beneficial). The few studies of adoption in wild goose populations indicate cost-neutrality or that there are small benefits to parents of adopting young. This agrees with studies of brood size, which suggest that large families provide benefits for goslings and parents alike. By contrast, most observed adoption attempts involve parental aggression against the lone gosling. However, incidental observations are likely to be biased towards adoptions that involve conspicuous behaviour, such as aggression, and might overlook inconspicuous adoptions. Studies of individually marked goslings are needed to identify the background of the adoption goslings in order to identify whether in geese, as in some larids and altricial species, adoption might be an active strategy of offspring to improve their fitness prospects. In addition, more experimental studies are needed to test predictions about the costs and benefits of large families in geese.